FATTY ACIDS, a-TOCOFEROL AND L-CARNITINE: THEIR RELATIONSHIPS IN TURBOT (Scophthalmus maxímus L. GROWTH: FIRST RESULTS. - Fernández-Pato, Carlos; Martínez-Tapia, Inmaculada; Sola, Esperanza (2013)
The effect that the administration of diets rich in essential fattyacids has on growth in weight of turbot (S. maxímus), contrasted with non-enriched diets supplemented with a-tocoferol, and at two different levels of administration of l-carnitine has be en studied. The weight of individual s corresponding to the different levels of treatment is analysed using MANOVA of repeated measures, resulting in significant differences between the different treatments, with p<O.OOl. An evaluation is made of the efficiency of each of the different treatments with respect to growth and body content in fat and protein. No